Performance evaluation of improved S3 inverter for micro-grid applications. (2023) - Vijayakumar, K.
Abstract: The project is envisioned to convert DC output combined from the micro grid as the common dc bus into AC voltage. S3 inverter is used to obtain appropriate sine wave as output. Inverter generally has high Total Harmonic Distortion (THD) and by using our implementation on this project, less THD could be achieved. This topology of the inverter has only three semiconductor switches, one with a large frequency and another with a fundamental frequency. Therefore, the inverter is designated the S3.